Quantitative and selective surface plasmon resonance response based on reduced graphene oxide-polyamidoamine nanocomposite for detection of dengue virus E-proteins - Sheh Omar, Nur Alia; Yap, Wing Fen; Abdullah, Jaafar; Sadrolhosseini, Amir Reza; Mustapha Kamil, Yasmin; Muhamad Fauzi, Nurul ‘Illya; Hashim, Hazwani Suhaila; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2020)
Dengue viral infection is one of the most common deadliest diseases and has become a recurrent issue for public health in tropical countries. Although the spectrum of clinical diagnosis and treatment have recently been established, the efficient and rapid detection of dengue virus (DENV) during viremia and the early febrile phase is still a great challenge. In this study, a dithiobis (succinimidyl undecanoate, DSU)/amine-functionalized reduced graphene oxide-–polyamidoamine dendrimer (DSU/amine-functionalized rGO–PAMAM) thin film-based surface plasmon resonance (SPR) sensor was developed for the detection of DENV 2 E-proteins. Different concentrations of DENV 2 E-proteins were successfully tested by the developed SPR sensor-based system. The performance of the developed sensor showed increased shift in the SPR angle, narrow full-width–half-maximum of the SPR curve, high detection accuracy, excellent figure of merit and signal-to-noise ratio, good sensitivity values in the range of 0.08–0.5 pM (S = 0.2576°/pM, R2 = 0.92), and a high equilibrium association constant (KA) of 7.6452 TM−1. The developed sensor also showed a sensitive and selective response towards DENV 2 E-proteins compared to DENV 1 E-proteins and ZIKV (Zika virus) E-proteins. Overall, it was concluded that the Au/DSU/amine-functionalized rGO–PAMAM thin film-based SPR sensor has potential to serve as a rapid clinical diagnostic tool for DENV infection.